Konsepsi H{adi>th Mukhtalif dan Metode Penyelesaiannya di Kalangan Ulama Fiqh - renanda-rezad montifani (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
H{adi>th is the main source of teachings after the Qur'an which comes from the Prophet, and everything that is conveyed by the Prophet is a revelation. However, in the h{adi>th sometimes there are still conflicts, disputes, or differences with other traditions or other syar'i arguments, which are called H{adi>th mukhtalif. Therefore, here we conduct a study of H{adi>th mukhtalif which is about the study of h{adi>th that seem contradictory, then compromise between the two or favor one of the two. This study is a very important requirement for every pious and faqih, in order to be able to know the importance of such h{adi>th. This can also inspire us indirectly, how we behave when we encounter traditions that contradict or differ from the existing arguments. Therefore, this article was written to discuss the methodology for resolving conflicting hadith among scholars of Fiqh which can help us to be able to behave and understand the hadiths that are dhohir contradict each other by using the right method.Keywords: H{adi>th mukhtalif, Conflicting Hadith, Scholars of Fiqh.